The Effect of Human Resources Training and Development on Increasing The Productivity of Fashion Sme Employees in Yogyakarta - Krismatuningsih Krismatuningsih; Nur Wening (Al-Makki Publisher, 2025)
This study aims to find out and describe the influence of HR training and development on the productivity of Fashion SME employees in Yogyakarta. This study uses a quantitative method. Data collection was conducted using a questionnaire given to 133 employees of Fashion SMEs at random in Yogyakarta. The bound variable (Y) in this study is the productivity of SME employees in the city of Yogyakarta while the independent variable 1 (X1) is training and the independent variable 2 (X2) is human resource development. The results showed that the contribution of the influence of independent variables (X1 and X2) together to the dependent variable (Y) had a significant influence of 31.9%. Partially, the training variable has a strong influence on the productivity of Fashion SME employees in Yogyakarta while the human resource development variable has a strong influence.